TINJAUAN TENTANG PELAYANAN WAITER/WAITRESS DI SKYLINE RESTAURANT IBIS HOTEL PADANG DENGAN PENDEKATAN CHSE - Politik Salakkirat; Yen Polisda (Jurnal Pariwisata Bunda, 2021)
This article aims at finding out the implementation of CHSE  by waiters and waitresses at Skyline Restaurant Ibis Hotel in serving the guests. CHSE, Cleanliness, Health, Safety and Environmental Sustainability, is the Indonesian government program through the Ministry of Tourism and Creative Economy to prevent  and control Corona Virus Disease 2019 (covid-19). The rationale is that the spread of Covid- 19 has already affected all sectors, one of which is the hotel industry. A hotel restaurant is assumed to be one of potential places to spread Covid-19 virus as it is a place where people gather. Therefore, a restaurant service needs to apply  the CHSE. The data were gained through interviews and observation. The findings of the research indicated that waiters and waitresses at Skyline Restaurant Ibis Hotel have already served the guests based on CHSE protocol for covid- 19.